2021
DOI: 10.1101/2021.02.01.429229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Voluntary alcohol consumption disrupts coupling of prefrontal cortical activity to arousal

Abstract: Alcohol use disorder (AUD) exacts a major personal, societal, and economic toll. Top-down control from the prefrontal cortex (PFC), a critical hub for decision making, executive, and other cognitive functions, is key for the regulation of alcohol consumption. Arousal exerts profound effects on cortical processing, allowing it to potentially modulate PFC functions relevant for alcohol consumption and AUD. Despite this, it is unclear whether and how arousal-mediated modulation of PFC circuits relates to voluntar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 112 publications
0
5
0
Order By: Relevance
“…Mice were induced to walk on a motorized treadmill (scheme, Fig. 1e), a condition known to elicit a global rise in calcium within cortical astrocytes due to the local release of norepinephrine (NE) that accompanies enhanced arousal 27,40,44 . Astrocytes throughout the imaging field in astro-GC3 mice exhibited transient increases in fluorescence (Fig.…”
Section: Multicore Fiber Optic Imaging Allows Visualization Of Astroc...mentioning
confidence: 99%
“…Mice were induced to walk on a motorized treadmill (scheme, Fig. 1e), a condition known to elicit a global rise in calcium within cortical astrocytes due to the local release of norepinephrine (NE) that accompanies enhanced arousal 27,40,44 . Astrocytes throughout the imaging field in astro-GC3 mice exhibited transient increases in fluorescence (Fig.…”
Section: Multicore Fiber Optic Imaging Allows Visualization Of Astroc...mentioning
confidence: 99%
“…However, as clinical goals shift towards personalized medication strategies, there is increasing need for preclinical models of alcohol use that capture individual differences and incorporate multimodal assessments of specific behaviors within the AUD spectrum [52,53]. At the same time, advances in neurotechnologies for interrogating in vivo cellular activity in real-time have rapidly transformed behavioral neurosciences but are often incompatible with established AUD models, resulting in a divergence of methodologies throughout the field [43,76,77]. Here, to address these issues, we establish an approach for Structured Tracking of Alcohol Reinforcement.…”
Section: Development Of Preclinical Models and Advancement Towards Cl...mentioning
confidence: 99%
“…Despite the advantages of these head-fixed techniques, as well as extensive research on alcohol consumption and ARD using quinine in freely moving mice, very little data exist regarding alcohol consumption and ARD in head-fixed mice. To date, it has been shown that head-fixed mice will voluntarily consume alcohol [46], but no studies have documented ARD using quinine in head-fixed mice. Furthermore, no studies have related head-fixed alcohol drinking and ARD to home-cage drinking patterns and ARD.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, these techniques make it possible to record from large portions of the cortical surface using widefield calcium imaging [42], to simultaneously record from and manipulate brain region level populations with two-photon calcium imaging and optogenetics [43], or record from thousands of neurons simultaneously across multiple brain regions using multiple high-density electrophysiology probes [44]. Furthermore, due to the stable positioning of the animal, these methods facilitate motion tracking of individual body parts [45] and advanced behavioral analyses [46][47][48][49][50][51][52][53][54][55], as well as the precise delivery of visual [56], auditory [57], and olfactory stimuli [58,59]. This improved precision reduces noise between behavioral data, stimuli, and neural activity in comparison to freely moving mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation